Inducing the international diffusion of carbon capture and storage technologies in the power sector - Daniel Vallentin (Wuppertal Institut für Klima, Umwelt, Energie, 2007)
Although CO2 capture and storage(CCS) technologies are heatedly debated, many politicians and energy producers consider them to be a possible technical option to mitigate carbon dioxide from large-point sources. Hence, both national and international decision-makers devote a growing amount of capacities and financial resources to CCS in order to develop and demonstrate the technology and enable ist broad diffusion.The presented report concentrates on the influence of policy incentives on CCS diffusion and examines the following research question: Which policy strategy is needed to stimulate the international diffusion of carbon capture and storage technologies in the power sector? Based on the analysis of innovation-specific (e.g. CCS competitiveness and compatibility), market-related (e.g. national CO2 discharges and storage capacities) and institutional determinants (e.g. existing national and international policy frameworks) of CCS diffusion, the paper discusses the suitability of various national and international policy instruments to induce the international deployment of CCS. Afterwards, three CCS diffusion paths are derived from fundamentally different carbon stabilisation scenarios which include climate policy measures to stimulate the adoption of CO2 mitigation technologies. – – Als Carbon Capture and Storage (CCS) wird die Abtrennung von Kohlendioxid aus Rauchgas-, Brenngas- oder Industriegasströmen und dessen anschließende langfristige Verwahrung in geeigneten Lagerstätten bezeichnet. Im Wuppertal Paper Nr. 162 geht Daniel Vallentin der Frage nach, welche Handlungsstrategien die internationale Diffusion von CCS-Technologien herbeiführen. In diesem Kontext stellt er unter anderem verschiedene Fallstudien sowie potenzielle Märkte für CCS-Technologien vor.
urn:nbn:de:101:1-200910086652
Keywords: 330; Umweltverträgliche Energiepolitik; Umwelttechnik; Innovationsdiffusion; Klimaschutz; Kohlendioxid; Kraftwerk; Luftreinhaltung; Welt